POTRET PENDIDIKAN MORAL DALAM NOVEL MERPATI BIRU KARYA ACHMAD MUNIF (THE PORTRAIT OF MORAL EDUCATION THROUGH THE NOVEL “BLUE DOVE” BY ACHMAD MUNIF) - Basuki Sarwo Edi (Balai Bahasa Sulawesi Utara, 2016)
This study aimed to describe the portrait of moral education through the novel “Blue Dove” by Achmad Munif, a picture of human life. Benefits Novel studies reveal facts as a source of public education. With novel reading materials can be used as study materials. Sources used in this study is novel Pigeons Blue Achmad Munif work. The method used deskriprif method.The results obtained in this study indicate that the novel Pigeons Blue Achmad Munif work has a theme of environmental influences determine the character “a figure Ken” in the struggle to survive, to struggle and hard work.